Blood Lead, Bone Turnover, and Survival in Amyotrophic Lateral Sclerosis - Fang, Fang (Am J Epidemiol, 2017)
Blood lead and bone turnover may be associated with the risk of amyotrophic lateral sclerosis (ALS). We aimed to assess whether these factors were also associated with time from ALS diagnosis to death through a survival analysis of 145 ALS patients enrolled during 2007 in the National Registry of Veterans with ALS. Associations of survival time with blood lead and plasma biomarkers of bone resorption (C-terminal telopeptides of type I collagen (CTX)) and bone formation (procollagen type I amino-terminal peptide (PINP)) were estimated using Cox models adjusted for age at diagnosis, diagnostic certainty, diagnostic delay, site of onset, and score on the Revised ALS Functional Rating Scale. Hazard ratios were calculated for each doubling of biomarker concentration. Blood lead, plasma CTX, and plasma PINP were mutually adjusted for one another. Increased lead (hazard ratio (HR) = 1.38; 95% confidence interval (CI): 1.03, 1.84) and CTX (HR = 2.03; 95% CI: 1.42, 2.89) were both associated with shorter survival, whereas higher PINP was associated with longer survival (HR = 0.59; 95% CI: 0.42, 0.83), after ALS diagnosis. No interactions were observed between lead or bone turnover and other prognostic indicators. Lead toxicity and bone metabolism may be involved in ALS pathophysiology.